Positioning Africa: the limits of perpetuation: an investigation of postcolonial Eurocentrism and its impact on the display of African art in Britain between 1995 and 2005 - Johnson, Kresta Tyler (My University, 2009)
Abstract: This research report analyses the extent to which Britain maintained a neo-colonial, Eurocentric mentality towards the arts of Africa over the course of the decade 1995 to 2005. Two exhibitions that focused on the arts of Africa were mounted in Britain during this period. Both of these exhibitions, used as case studies in this research report, clearly demonstrated that entrenched stereotypes persist regarding Africa’s artistic output. The africa95 and Africa 05 programmes highlighted the fact that African artists are valued in Western centres primarily for their ‘difference’, continually being marginalised through omnibus narratives that single out African artists as producing the work of the Other. ‘Traditional’ African art is equated with ‘authentic’ African art and the work of contemporary African artists is either compared with the ‘traditional’, or negated for being too influenced by Western aesthetics. Discourses around identity and representation of African artists in the West have been impacted by numerous factors such as the growth and increased profile of the African diaspora. While entrenched mindsets in the West towards African art are beginning to shift, ultimately the identity of contemporary African artists is framed within very narrow parameters that have been created by Western art centres and imposed upon African artists. In this context, the insular British cultural establishment has proven particularly resistant to change. The centre/periphery paradigm serves as a protective measure for British cultural identity. However, even as subtle shifts away from this perspective begin and the initial stages of an acceptance of contemporary African art is revealed, it is nonetheless a very limited advancement that still revolves around a small number of British institutions and curators who set the parameters of the discourse. In summary, this analysis of the decade under review reveals that very little has changed regarding the positioning of African art in Britain.